2017
DOI: 10.1002/pen.24545
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of PES/CA microporous membranes via reverse thermally induced phase separation process

Abstract: The blend polyethersulfone (PES)/cellulose acetate (CA) flat‐sheet microporous membranes were prepared by reverse thermally induced phase separation (RTIPS) process. The effects of CA content and coagulation bath temperature on membrane structures and properties were investigated in terms of membrane morphology, water contact angle, permeation performance, and mechanical properties. The cloud point results indicated that the cloud point decreased with the increasing content of CA. When the coagulation bath tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…As it can be seen in Figs. and , all the investigated ternary systems show small miscible region (small area of region I) and thus gelation is the main mechanism for preparation of membranes and thus it is expected to form a relatively porous top layer that makes it appropriate for using in microfiltration and ultrafiltration processes . These results are completely in agreement with the SEM graphs presented in Figs.…”
Section: Resultssupporting
confidence: 87%
“…As it can be seen in Figs. and , all the investigated ternary systems show small miscible region (small area of region I) and thus gelation is the main mechanism for preparation of membranes and thus it is expected to form a relatively porous top layer that makes it appropriate for using in microfiltration and ultrafiltration processes . These results are completely in agreement with the SEM graphs presented in Figs.…”
Section: Resultssupporting
confidence: 87%
“…Table illustrated a comparison of our study results with other reported literatures on membrane performance. When compared with some published PVA modified membranes [21,32,40,42,54–56], the performances of our fabricated membranes were comparable or even better, the FRR, contact angle, antifouling property, and BSA rejection of our membranes are more favorable than the reported ones. In General, the membranes made in PVA/water coagulation bath display significant performances in hydrophilicity and antifouling performance.…”
Section: Resultsmentioning
confidence: 48%
“…In light transmittance experiment, a self‐designed instrument was used as stated by Li and co‐workers . A light source of laser was placed above the coagulation bath which contained different content PVA aqueous solutions.…”
Section: Methodsmentioning
confidence: 99%
“…The pressure‐resistant property of UF membranes has become an important research direction for researchers. At present, researchers mainly focus on preparation of UF membranes by various materials of high performance, such as polyethersulfone (PES), polysulfone (PSf), polyacrylonitrile, poly(vinylidene fluoride) (PVDF), and ceramic . An and coworkers obtained a PSf membrane with fully sponge‐like structure showing high flux and good pressure‐resistant property by adding ethanol and PVP‐k90 mixed additives into the PSf/dimethylacetamide (DMAC) casting solution.…”
Section: Introductionmentioning
confidence: 99%